2020
DOI: 10.1007/978-3-030-57404-8_10
|View full text |Cite
|
Sign up to set email alerts
|

KidsDoodlePass: An Exploratory Study of an Authentication Mechanism for Young Children

Abstract: Textual passwords are problematic for young children, whose cognitive, memory and linguistic capabilities are still developing. A possible alternative to using text for authentication systems for young children is drawings. In this paper, we describe an authentication system called KidsDoodlePass, which use simple drawings ("doodles") that the children themselves create. An initial evaluation of the system was undertaken with 19 children aged 6 to 9 years of age. Success of logging in with KidsDoodlePass was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Alkhamis et al [2] study found that children between the age of 6-9 were able to effectively authenticate with a doodle they created, and this persisted in subsequent trials. Assal et al [6] assessed usability and preference for graphical passwords for children and adults, finding a preference for graphical authentication, with children most effectively recalling distinct objects like an animal, this was also found by Stewart et al [53] in their study with younger children.…”
Section: Graphical Passwords (Paper Ids: P11 P13 P23 P25)mentioning
confidence: 96%
See 3 more Smart Citations
“…Alkhamis et al [2] study found that children between the age of 6-9 were able to effectively authenticate with a doodle they created, and this persisted in subsequent trials. Assal et al [6] assessed usability and preference for graphical passwords for children and adults, finding a preference for graphical authentication, with children most effectively recalling distinct objects like an animal, this was also found by Stewart et al [53] in their study with younger children.…”
Section: Graphical Passwords (Paper Ids: P11 P13 P23 P25)mentioning
confidence: 96%
“…The papers in this review placed greater importance on memory and literacy whilst potentially overlooking problem solving in password generation which could be vital in solving problems with password generation. Children have been observed to have difficulty with authentication and the research suggests memory, attention, and literacy most prominently, the experiences of authentication may then be often negative for children, and this is proposed as affecting the way in which passwords will then be created in the future [2]. It is likely then, that children will choose to create weak passwords to improve authentication experiences, and thus continuing insecure password practice.…”
Section: Rq4: the Role Of Cognitionmentioning
confidence: 99%
See 2 more Smart Citations